Salem's lot [videorecording (Blu-Ray)] - Monash, Paul, 1917-2003; Soul, David; Mason, James, 1909-1984; Kerwin, Lance, 1960-; Ayres, Lew, 1908-1996; Bedelia, Bonnie, 1946-; King, Stephen, 1947- (Warner Bros. Entertainment, 2016)
The complete miniseries based on Stephen King's novel about a sleepy New England village which is infiltrated by evil.